World Hunger and the Global Economy: Strong Linkages, Weak Action - Jennifer Clapp (Journal of International Affairs, 2014)
This paper probes some of the global economic forces that have contributed to the ongoing precarious global food security situation, especially in the years since the 2007 to 2008 food crisis. Since the crisis hit at a time when global food production per capita was rising, it is important that policies addressing hunger incorporate dimensions beyond food production. There has been some acknowledgement of the role of global economic forces in the food crisis by global policymakers, but global food security initiatives still largely emphasize increased food production over other measures. The paper concludes that more needs to be done to ensure that the rules that govern the global economy--especially those regarding international trade, finance, and investment--do not work against the goal of food security.